Ergonomisk förbättring vid hanteringen av L1-prover på provhanteringen : Förstudie på SSAB EMEA AB i Luleå - Pettersson, Stefan (2012)
The staff at the sampling handling at SSAB EMEA AB in Luleå is currently experiencing some Musculoskeletal disorders (MSD) due to manual handling of the L1 samples. Some MSDs has been experienced for some years and to reduce the risk of MSDs there is a need for change in work operations. The project is limited to address the tasks involved in the workshop on the handling of samples and includes only the handling of the L1 samples. The project aims both to present a number of concepts for how the operations on the sample handling can be improved from a ergonomic perspective and identify the work environment at the department for sample handling with regard to lightning and noise. In order to define the present situation in the department of sample handlings three different ergonomic analyzes were used; Ergonova, RULA and REBA. Based on the analysis the operations; Unloading the car, Slag tapping and Unloading from the acid cabinet was the worst result and thus affected the workloads greatest. In addition to these operations were also manual lifting and transporting a huge work pressure. Totally 13 pieces of concept proposals divided into work phases; Unloading the car, Slag tapping, Unloading from the acid cabinet and Transport in the workshop was generated. The concept proposals were evaluated against a specification of demands for each work phase and the winning concept proposal for each work phase was further developed. The lighting study consisted of measurements of illuminance and luminance, and control of light fittings in the location and shadowing at the workstations. The result of measurements of illuminance shows that the majority of areas in the workshop do not achieve the recommended illuminance of 500 lux. The measurements of luminance compared to the recommended luminance ratio 5:3:1, indicating that all the work stations have an incorrect luminance ratio. The noise measurements were based on the equivalent noise level, maximum level of noise and impulse peak value and compared to Arbetsmiljöverkets ...